Reconstructive Options for Oncologic Posterior Trunk Defects: A Review - Behr, Björn; Wagner, Johannes M.; Wallner, Christoph; Harati, Kamran; Lehnhardt, Marcus; Daigeler, Adrien (Frontiers in Oncology, 2016)
After oncological tumor resections at the back, large defects can remain that depending on the size and location may require flap coverage and represent reconstructive challenges to plastic surgeons. Flap selection includes the entire armamentarium of coverage including transposition flaps, perforator flaps, pedicled muscle flaps and free flaps. Most defects can be closed and reconstructed with local or pedicled muscle flaps. In our hands, sufficient closure could be obtained with all techniques, except the latissimus dorsi turn-over flap. Thereupon, an algorithm for closure of posterior trunk defects related to the anatomical region is proposed.